Development of Information Technologies, Planned Obsolescence and Modification of the Life-Cycle of the CAD/CAM/CAE Systems - Milchev, Galin; Miltchev, Radoslav (European Journal of Sustainable Development, 2018)
Contemporary production is impossible without the contemporary tools for its automatisation. The development of information technologies has created prerequisites for an alteration of the industrial paradigm from mass production towards individualised production. The rapid advancement and continuous improvement of technology are the reason why computer software as well as many other intangible assets, among which are the CAD/CAM/CAE systems, to be highly susceptible to technological obsolescence. Determining the duration of their useful life depends on the opportunities for the onset of risk events that lower the length of the time period in which they generate revenue for the business ?nterprise. The object of study in this article are the processes of physical, moral and planned obsolescence of the basic component of computer-aided productions, namely machines with digitally programmed control, as it is one of the main directions of realising the reindustrialisation processes. Examined are both the main trends in the development of that part of assets of corporations, and the changes in their life-cycle. On the basis of research and comparative methods, an assessment is made of the opportunities for eliciting maximum benefits for small and medium-sized enterprises by achieving a synergic effect between the processes of moral obsolescence, the development of information and communication technologies, reindustrialisation and the formation of the economy structure on both a national and a global level. With that it is possible for a reversive process to be achieved, of transforming the capital costs for tangible and intangible assets into operating costs. Key words: planned obsolescence, life-cycle, information technologies, CAD/CAM/CAE.